Consumption of Big Game Remains by Scavengers: A Potential Risk as Regards Disease Transmission in Central Spain - Carrasco-Garcia, Ricardo; Barroso, Patricia; Perez-Olivares, Javier; Montoro, Vidal; Vicente, Joaquín (Frontiers in Veterinary Science, 2018)
Understanding the role that facultative scavenger species may play in spreading infectious pathogens, and even becoming reservoirs for humans, domestic and wild ungulates or, on the contrary, preventing the spread of disease, requires a prior understanding of the pattern of carrion scavenging in specific scenarios. The objectives of this paper are: i) to describe the guild of vertebrate scavengers and ii) to study the species-specific, habitat and management-related factors involved in the usage of gut piles in South Central Spain (SCS), a tuberculosis (TB) endemic area. We used camera trapping at 18 hunting piles on 7 hunting estates. A total of 8 bird and 5 mammal taxa were detected at the remains of hunting piles. The most frequently detected species in terms of number of gut piles visited (78%) and scavenged (61%) was the red fox Vulpes vulpes, followed by the griffon vulture Gyps fulvus (56% as regards both presence and scavenging) and the raven Corvus corax (61 and 39% as regards presence and scavenging, respectively). We evidenced that griffon vultures accounted for most of the scavenging activity in open habitats, while facultative mammal scavengers, red fox and wild boar Sus scrofa made the highest contribution to scavenging in vegetation-covered habitats. In the case of wild boar, the gut piles deposited during the evening and night favoured higher rates of scavenging, while the opposite pattern was observed for griffons. Overall, our findings suggest that when disposing of hunting remains in areas of risk as regards disease transmission it is particularly important to consider the access that facultative mammals, and especially wild boar, have to material, while the presence of the resource needs to be safeguarded to protect specialist scavengers of conservation value. These results are of particular relevance in the case of wild boar in the current context of re-emerging TB and emerging African Swine Fever (ASF) in Europe.